Intensification of antiretroviral treatment with raltegravir for pregnant women living with HIV at high risk of vertical transmission - Thanyawee Puthanakit; Nattawan Thepnarong; Surasith Chaithongwongwatthana; Suvaporn Anugulruengkitt; Orawan Anunsittichai; Tuangtip Theerawit; Sasiwimol Ubolyam; Chitsanu Pancharoen; Praphan Phanuphak (Elsevier, 2018)
Objectives:The rate of vertical HIV transmission for women at high risk of HIV transmission stands at approximately 7.6%. In the present study we describe infant infection rates in women who had received raltegravir (RAL) intensification during pregnancy to a standard three-drug antiretroviral (ART) regimen in Thailand.Methods:This prospective cohort study enrolled HIV-1-positive pregnant women at high risk of vertical transmission, as defined by (1) ART initiation at a gestational age (GA) ≥32 weeks or (2) HIV-1 RNA >1000 copies/mL at GA of 32-38 weeks while on ART. Women received a standard three-drug ART regimen with RAL intensification (400 mg twice daily) until delivery and continued on a three-drug ART regimen after delivery. Plasma HIV-1 RNA testing was performed before intensification and at delivery. Infant HIV-1 status was determined using DNA PCR at birth, and at 1, 2 and 4 months of life.Results:Between February 2016 and November 2017, 154 pregnant women on ART were enrolled into the study with a median CD4 cell count and plasma HIV-1 RNA level of 382 cells/mm3 and 4.0 log10copies/mL, respectively. The three-drug combination consisted of either a lopinavir/ritonavir- (53%) or efavirenz-based (43%) regimen. Median GA at time of RAL initiation was 34 weeks (interquartile range [IQR] 33-36) and median duration was 21 days (IQR 8-34). The proportion of women who had a plasma HIV-1 RNA >50 and >1000 copies/mL at delivery was 45% and 76%, respectively. There were six infants with HIV infection, three in utero and three peripartum. Overall vertical transmission rate was 3.9% (95% confidence interval [CI] 1.4-8.2).Conclusion:The majority of high-risk pregnant women living with HIV-1 who had received RAL intensification achieved viral suppression at delivery with a relatively low rate of vertical transmission. This intensification strategy represents an option for prevention in HIV-positive women at high risk of vertical transmission.